Korupsi dan Hadiah Dalam Kajian Undang-Undang Nomor 20 Tahun 2001 - Mustakid, Dodo; Heriyanto, Arif (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2024)
This act of corruption continues and ironically this act is mostly carried out by officials who have positions or positions that are used as a means to abuse the authority they have for their own benefit or the corporation. corruption occurs in a widespread and systematic way, not only detrimental to the state's finances and economy, but also a violation of the rights of the community at large in the economic and social spheres. Law No. 20 of 2001 the definition of corruption is: